Association between Stable Coronary Artery Disease and In Vivo Thrombin Generation - Benjamin Valente-Acosta; Manuel Alfonso Baños-González; Marco Antonio Peña-Duque; Marco Antonio Martínez-Ríos; Leslie Quintanar-Trejo; Gad Aptilon-Duque; Mirthala Flores-García; David Cruz-Robles; Guillermo Cardoso-Saldaña; Aurora de la Peña-Díaz (Cardiology Research and Practice)
Background. Thrombin has been implicated as a key molecule in atherosclerotic progression. Clinical evidence shows that thrombin generation is enhanced in atherosclerosis, but its role as a risk factor for coronary atherosclerotic burden has not been proven in coronary artery disease (CAD) stable patients. Objectives. To evaluate the association between TAT levels and homocysteine levels and the presence of coronary artery disease diagnosed by coronary angiography in patients with stable CAD. Methods and Results. We included 95 stable patients admitted to the Haemodynamics Department, including 63 patients with significant CAD and 32 patients without. We measured the thrombin-antithrombin complex (TAT) and homocysteine concentrations in all the patients. The CAD patients exhibited higher concentrations of TAT (40.76 μg/L versus 20.81 μg/L, p=0.002) and homocysteine (11.36 μmol/L versus 8.81 μmol/L, p<0.01) compared to the patients without significant CAD. Specifically, in patients with CAD+ the level of TAT level was associated with the severity of CAD being 36.17 ± 24.48 μg/L in the patients with bivascular obstruction and 42.77 ± 31.81 μg/L in trivascular coronary obstruction, p=0.002. Conclusions. The level of in vivo thrombin generation, quantified as TAT complexes, is associated with the presence and severity of CAD assessed by coronary angiography in stable CAD patients.